Visual Culture Art Education: An Approach to Art Learning in the 21st Century - Ratih Ayu Pratiwinindya; Agus Cahyono; Tjetjep Rohendi Rohidi; Eko Sugiarto (International Conference on Science, Education, and Technology, 2022)
Abstract. In the 21st century, life has changed a lot, both in society and in the world of education. The 21st century is also known as the knowledge age. In that era, almost all efforts to fulfill the necessities of life in various aspects were based on knowledge and technology. Referring to the P21 Framework (Partnership for 21st century) it is explained that there are skills, knowledge and expertise that must be mastered so that students can be successful in their work career life. Many careers are still underestimated and may not yet exist and be introduced in the curriculum. With the development of technology, many new careers and professions have sprung up, such as content creator, video editor, cinematographer, videographer, illustrator and other new professions that are urgently needed. In the context of art learning, visual culture may play an important role in raising this awareness. In the art education paradigm, it does not emphasize that all students will be proficient at drawing or like to paint, but through art education, especially with a visual culture approach, it gives an idea to students that there are many alternative ideas and new opportunities that are closer to their daily lives for example in terms of branding, design, advertising, video games, fashion, logo and design. Adding visual culture to the curriculum, is a concept that is inevitable that not only makes students more motivated in learning but also allows students to see other career paths that they might choose in life.